Abiraterone acetate: oral androgen biosynthesis inhibitor for treatment of castration-resistant prostate cancer - Rosenberg JE; Rehman Y (Dove Medical Press, 2012)
Yasser Rehman1, Jonathan E Rosenberg21Division of Hospital Medicine, UMass Memorial Healthcare, Worcester, MA, USA; 2Lank Center for Genitourinary Oncology, Dana Farber Cancer Institute, Harvard Medical School, Boston, MA, USAAbstract: Prostate cancer is the second leading cause of cancer death in men in the US and Europe. The treatment of advanced-stage prostate cancer has been androgen deprivation. Medical castration leads to decreased production of testosterone and dihydrotestosterone by the testes, but adrenal glands and even prostate cancer tissue continue to produce androgens, which eventually leads to continued prostate cancer growth despite castrate level of androgens. This stage is known as castrate-resistant prostate cancer (CRPC), which continues to be a challenge to treat. Addition of androgen antagonists to hormonal deprivation has been successful in lowering the prostate-specific antigen levels further, but has not actually translated into life-prolonging options. The results of several contemporary studies have continued to demonstrate activation of the androgen receptor as being the key factor in the continued growth of prostate cancer. Blockade of androgen production by nongonadal sources has led to clinical benefit in this setting. One such agent is abiraterone acetate, which significantly reduces androgen production by blocking the enzyme, cytochrome P450 17 alpha-hydroxylase (CYP17). This has provided physicians with another treatment option for patients with CRPC. The landscape for prostate cancer treatment has changed with the approval of cabazitaxel, sipuleucel-T and abiraterone. Here we provide an overview of abiraterone acetate, its mechanism of action, and its potential place for therapy in CRPC.Keywords: CRPC, abiraterone, CYP17, inhibitors, androgens, castration resistant prostate cancer